Caring for pregnant women with diagnosis of fetal malformation. - Escobar Marín, Alcira; Hernández Sampayo, Luzmila; Morales Viana, Liliana Cristina; Vásquez Truissi, Martha Lucía; Argote Oviedo, Luz Ángela (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To describe the beliefs, experiences, and practices of caring for pregnant women with diagnosis of fetal malformation. Methodology. Focused ethnography with the participation of eight women older than 18 years of age with diagnosis of fetal malformation and whose parturition occurred in a tier III hospital. The sample size was defined per data saturation. The information was obtained through in-depth interviews and analysis with the Spradley methodology. Results. The women endured the experience as a painful process, from which they manifested fear, uncertainty, and culpability regarding the diagnosis. This situation led them to using coping strategies like faith in God, adhering to recommendations from healthcare personnel, and carrying out cultural practices. Because the diagnosis was made during the advanced stage of the pregnancy, the participants had to continue with the gestation and adapt the self-care practices during this period. Conclusion. Self-care practices and relationships were evidenced among the women and the social support networks and the healthcare system, which favored confronting this situation by the pregnant women and their families, which permitted their carrying the gestation until the end.